Analysis of factors related to stunting prevention behavior in toddlers - Asmalinda, Andi; Rahayu, Mesra (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Stunting or failure to grow is a condition that describes the nutritional status of a child with a chronic nature during the growth and development of the child from the beginning of life, characterized by a child's height that is shorter than the age. Objective: This study analyzes factors related to stunting prevention behavior in children under five. Methods: This type of research is an observational study with a Cross-Sectional Study approach, where the researcher only observes a phenomenon at a certain point in time that explains the relationship between one variable and another variable in the studied population. Data collection was carried out using a questionnaire. The sample of this study is 20 mothers under five. Data analysis was carried out using Fisher's Exact Test. Result: The results of the Fisher's Exact Test statistic test obtained a value of p-value = 0.018; family support obtained a value of p-value = 0.004; sociocultural obtained a value of p-value = 0.004; Knowledge obtained a value of p-value = 0.000 < an alpha value (Î± = 0.05). Conclusion: This study shows a significant relationship between Education, family support, socio-culture, Knowledge, and stunting prevention behavior in children under five. Maternal Education, family support, sociocultural aspects, and mothers' Knowledge are essential in stunting prevention efforts.